2016
DOI: 10.1093/humrep/dew145
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics, safety and tolerability of an intravaginal ring releasing anastrozole and levonorgestrel in healthy premenopausal women: a Phase 1 randomized controlled trial

Abstract: 14 March 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 35 publications
4
40
0
1
Order By: Relevance
“…In order to obtain a release rate that is above this cutoff for most subjects, 300 μg/d was chosen as the minimally effective dose. Selection of the highest release rate of ATZ was not limited by safety issues because there were no safety concerns at the highest dose level in the phase 1 clinical study . The highest release rate for ATZ was, however, limited by the technical feasibility of using only 1 IVR of an acceptable size in combination with 40 μg/d LNG and therefore amounted to 1050 μg/d, which was chosen as the maximum dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain a release rate that is above this cutoff for most subjects, 300 μg/d was chosen as the minimally effective dose. Selection of the highest release rate of ATZ was not limited by safety issues because there were no safety concerns at the highest dose level in the phase 1 clinical study . The highest release rate for ATZ was, however, limited by the technical feasibility of using only 1 IVR of an acceptable size in combination with 40 μg/d LNG and therefore amounted to 1050 μg/d, which was chosen as the maximum dose.…”
Section: Discussionmentioning
confidence: 99%
“…Full details of participants as well as inclusion and exclusion criteria for this study are published elsewhere . Briefly, the study consisted of a screening visit, pretreatment cycle, treatment, and follow‐up.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the tampons were used in group D on days 20 to 23. No parallel reference group was available for this period; however, the continuous, stable concentration–time profiles of ATZ and LNG for this period could be seen in a previous study . Interestingly, the concentrations of ATZ and LNG appeared to be slightly decreased during the use of tampons.…”
Section: Discussionmentioning
confidence: 81%
“…One phase 1 study has been completed in Europe investigating the pharmacokinetics (PK), pharmacodynamics (PD), safety, and tolerability of IVRs delivering ATZ/LNG in healthy, ovulating women aged 18–35 years . The results showed that doses of 40 μg LNG/day combined with up to 1050 μg ATZ/day reached the anticipated exposure levels for both drugs …”
mentioning
confidence: 99%
“…Intravaginal ring which consists of Anastrozole and Levonogestrel has been brought into experimental practice and it was proposed that constant drug plasma levels can be achieved due to the continuous release of drug from the intravaginal ring. The efficacy of intravaginal drug delivery was uncertain but it was shown that by avoiding the first-pass metabolism in the liver, equivalent efficacy could be accomplished and unwanted side effects were reduced [31,32]. In a study done on cynomolgus monkeys using the vaginal rings, the circulating estrogen level was found to be reduced by at least 30% without leading to ovarian hyperstimulation caused by the pituitary counter regulatory pathway [33].…”
Section: Pain In Endometriosismentioning
confidence: 99%